2008
DOI: 10.1016/j.amjcard.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Cardiomyocyte Apoptosis in Patients With Acute Myocardial Infarction of the Left Ventricular Wall

Abstract: Cardiac remodeling after acute myocardial infarction (AMI) is characterized by molecular and cellular mechanisms involving both the left (LV) and right ventricular (RV) walls. Cardiomyoycte apoptosis in the peri-infarct and remote LV myocardium has a central role in cardiac remodeling. Whether apoptosis also occurs in the right ventricle of patients with ischemic heart disease has not been investigated. The aim of the present study was to investigate the presence of cardiomyocyte apoptosis in the right ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…The occurrence of RV dysfunction and failure has been associated with a poor prognosis after MI, however only few studies have systematically addressed RV remodeling following MI [1,32]. Our study was conducted to investigate RV function following LV MI in rats that developed or not HF.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of RV dysfunction and failure has been associated with a poor prognosis after MI, however only few studies have systematically addressed RV remodeling following MI [1,32]. Our study was conducted to investigate RV function following LV MI in rats that developed or not HF.…”
Section: Discussionmentioning
confidence: 98%
“…In this model of nonreperfused myocardial infarction, mortality is high, and cardiac remodeling is global and involves the infarct and border zones as well as the unaffected remote left ventricle and the right ventricle (Abbate et al, 2008a;Toldo et al, 2011). Blockade of A 2B AdoR seemed to have no effect on the infarct size, whereas A 2B AdoR blockade may have prevented thinning and stretching of the infarct and border zones (infarct expansion) and protected the border zone and the remote myocardium, as evidenced by an improvement in both left and right ventricular dimensions and, importantly, LV function.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the findings of Abbate et al (20) may be helpful in explaining the mechanism of RV involvement. Abbate et al showed remarkable RV cardiomyocyte apoptosis in the setting of acute myocardial infarction of the left ventricular wall.…”
Section: Discussionmentioning
confidence: 91%
“…In the literature, postmortem studies mention RV involvement after left ventricular infarction (19). Abbate et al found RV cardiomyocyte apoptosis in patients with anteroseptal myocardial infarction and RV-free wall involvement upon histopathological examination (20). Bodi et al showed RV involvement after AMi in an animal model via MRI (8).…”
Section: Discussionmentioning
confidence: 99%